Closing the Gap between Financial Literacy and Financial Inclusion - Pandeirot, Lanemey Brigitha; Aseng, Andrew Christian (Jurnal Informatika Ekonomi Bisnis, 2024)
Nowadays many people still trapped into some financial fraud because of lack of financial literacy. On the other hand, the Indonesian government are trying to increase public financial literacy rate in order to reach the financial inclusion rate through Strategi Nasional Literasi Keuangan Indonesia (SNLKI). Thus, this systematic literature review was done to discuss factors influence financial literacy so that it can be increased and cope with the financial inclusion rate. Several journal articles and related sources were selected and analyzed. The results found that financial literacy does affect financial inclusion and for the former rate be increased to close the gap with the latter, there are five factors need to consider, namely: formal education, socialization, family, government regulation, and use of financial technology. There are some recommendations of strategy for each factor that are discussed in hoping to help increase public financial literacy and support the government program through SNLKI.